Quantum calculations of the photoelectron spectra of the OH−·NH3 anion: implications for OH + NH3 → H2O + NH2 reaction dynamics. Issue 11 (17th March 2021) - Saito, Kohei; Sugiura, Yutaro; Miyazaki, Takaaki; Takahashi, Yukinobu; Takayanagi, Toshiyuki
Abstract : Quantum dynamics calculations were performed to analyze the experimentally measured photoelectron spectrum of the OH − ·NH3 anion complex. Abstract : We present the results of quantum dynamics calculations for analyzing the experimentally measured photoelectron spectra of the OH − ·NH3 anion complex. Detachment of an excess electron of OH − ·NH3 initially produces a molecular arrangement, which is close to the transition-state structure of the neutral OH + NH3 → H2 O + NH2 hydrogen abstraction reaction due to the Franck–Condon principle, and thus finally leads to the OH + NH3 or H2 O + NH2 asymptotic channel. We used both the path integral method and the reduced-dimensionality quantum wave packet method to simulate the photoelectron spectra of the OH − ·NH3 anion. The calculated spectra were found to be in qualitative agreement with the experimental spectra. It was found that the photodetached complex mainly dissociates into the OH + NH3 channel; however, we found that the hydrogen exchange process also contributes to the photodetachment spectra.